Distributional characteristics of epiphytic bryophytes and the relationships with environmental factors in Hangzhou City - SHENG Wei; MO Yaying; HU Zhongjian; RU Yalu; WU Yuhuan (浙江大学学报. 农业与生命科学版)
Based on the investigation of the diversity and ecological factors of epiphytic bryophytes from 21 sampling sites (including 178 trees, 2 848 quadrats) in Hangzhou City, 48 species belonging to 37 genera in 22 families of epiphytic bryophytes were recognized. The two-way indicator species analysis (TWINSPAN) results showed that the selected 21 sites could be divided into five groups with different habitats. The sample group Ⅳ had 21 species of bryophytes with the highest total coverage as 21.985 2%, and the sample group Ⅴ only had Lindbergia sinensis, with the smallest total coverage as 1.368 8%. The results reflected positive correlation between the distribution of epiphytic bryophytes and habitat types. Canonical correlation analysis (CCA) results showed that epiphytic bryophytes tended to be distributed on the southern side and the base of the trunk. There was no significant specificity between epiphytic bryophytes and the height and orientation of the trunks. The position of epiphytic trunks in urban trees was not strictly required for epiphyte bryophytes, indicating that the trunk’s orientation and height have no significant effect on the distribution of epiphytic bryophytes in Hangzhou City. It is implied that most species of epiphytic bryophytes are not closely related to orientation and height factors.